Good Intentions Are Not Enough. Uncovering Hegemonic Practice While Trying to Create Change - Ericka Turley (Adult Education Research Conference, 2014)
This paper presents the findings of a participatory action research project that challenges the idea of what it means to be the difference. The purpose was to identify a shared problem relating to equity and social justice in the workplace and then act to address the problem.